Youth social innovation during the COVID-19 pandemic in the Philippines: a quantitative and qualitative descriptive analyses from a crowdsourcing open call and online hackathon. Issue 3 (20th May 2022) - Ulitin, Allan; Mier-Alpaño, Jana Deborah; Labarda, Meredith; Juban, Noel; Mier, Abigail Ruth; Tucker, Joseph D; Tang, Weiming; Auplish, Mallika; Chan, Po-lin
Abstract : Introduction: Young people have played a pivotal role as part of the COVID-19 response, including developing health messages and social innovations. Social innovation in health engages multiple stakeholders in linking social change and health improvement. The study examined the feasibility of youth ideas and innovations to address the impacts of the COVID-19 pandemic using quantitative and qualitative descriptive analyses. Methods: In partnership with the WHO, academic institutions, youth organisations and civil society groups, we conducted a crowdsourcing open call among Filipino youth (15–30 years old) using a structured Special Programme for Research and Training in Tropical Diseases/Social Innovation in Health Initiative process. The open call had three categories: youth voices to cocreate the post-COVID-19 world (entries were texts, images, videos and music), youth-led COVID-19 social innovations, and youth-led social innovations not related to COVID-19 . Each submission was evaluated by three independent judges. Finalists were selected in each of the categories alongside four grand winners. All finalists were invited to attend a 1 day online civic hackathon. Results: We received a total of 113 entries ( youth voices to cocreate the post-COVID world =76; youth-led COVID-19 social innovations =17; youth-led social innovations not related to COVID-19 =20). Twelve entries focused on youth mental health during the pandemic. The online hackathon provided the participants mentorship for further development of their ideas. Finalists were able to produce draft health communication campaigns and improved social innovations. Conclusion: Many Filipino youth created exceptional entries in response to the open call. This suggests the feasibility of including youth voices in strategic planning processes. A global youth social innovation call is recommended.